PENGGUNAAN LOGIKA DALAM BUKU YUK BERHIJAB! KARYA FELIX SIAUW - Supriyadi, Supriyadi; Yulantomo, Aris (Perspektif, 2016)
This research is entitled " The Use of Logic in Yuk berhijab! By Ustad". The problem in thisresearch is how the use of logic induction, deduction, syllogism, the proposition, decision,analogy, and definitions used in the book berhijab Yuk! Ustad works of Felix Siauw. Thisstudy aimed to collect data and information induction, deduction, syllogism, the proposition,decision, analogy, and definitions used in the book Yuk berhijab! Ustad works of Felix Siauw.The theory that the authors use the, Ministry of Education (2008), Suhandang (2009),Rachmat (2011), Keraf (2006), Abidin (2002), Mundiri (2014), and Ranjabar (2014). Thepopulation in this study are all phrases that contain the logic in the book "Let hijab!" By FelixSiauw which consists of 140 pages, with the number of Chapter consists of 9 chapters. Themethod used is descriptive with qualitative approach and the type of research library (LibraryResearch). Conclusion. Induction of this research that found as many as 11 data or 7%.Deduction found as many as 10 data, or 6%. Syllogism as much as 4 data or 3%. Propositionfound as many as 11 data or 7%. The decision found as many as 55 of data, equivalent to35%. The analogy of the data found as many as 30 or 19%. And the definition of the data asmuch as 36 or 23%.